Donald Trumpâ€™s Muslim Banning in Two Micâ€™s Articles: A Transitivity Analysis - Rifah, Rifah; Yatmikasari, Ika (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2018)
AbstractMuslim banning issued by Donald Trump in his early presidency has become a controversial policy in US. It triggers various reaction both on the street and in the media. Mic of US is one of them that provide citizenâ€™s opinion on the issue. This study aims at revealing the writers of two Mic articlesâ€™ view on Donald Trump and on the issue related to Muslim banning itself by means of transitivity analysis, one metafunction in Systemic Functional Grammar. It also observes the different view (if any) between the two articles on the person and the issue they discuss. The analysis on process types and circumstances of the clauses in both articles results in: the writerâ€™s disagreement and dislike on Donald Trump and the policy in the article entitled Can Donald Trump ban all Muslims? Hereâ€™s what to know about his awful proposition; and the writerâ€™s support on Donald Trump and the issue in the second article entitled Donald Trump Calls for â€œA Total and Complete Shutdownâ€ of Muslims Entering the US.